Karakteristik Perawat dan Perilaku Keselamatan Kerja Perawat di RSUD Depok : Nurse Characteristics and Occupational Safety Behavior of Nurses at Depok Regional Hospital - Zifriyanthi Minanda Putri; Hanny Handiyani; Efy Afifah (Fakultas Keperawatan Universitas Andalas, 2016)
Hospital as a health care facility can be a dangerous place and a high risk to safety. Nursing personel who work continuously provide nursing care in hospital continuously for 24 hours every day at risk of illness and accidents. This study aims to identify the characteristics of the relationship of nurses with nurses work safety behavior. This study was a descriptive cross sectional approach. The results showed no association between nurse characteristics include age, gender, education, employment, and training with the nurses work safety behavior. The hospital is expected to provide wider opportunities for nurses to continue their education to a higher level, and organizes regular socialization and training related to safety of nurses in improving the safety behavior of nurses.